Edukasi dan Pencegahan Hipertensi pada Lansia di Panti Wredha Widhi Asih Surakarta - Gracesya Sherly Euodia Sari; Eleonora Febi Audystia; Fabio Christ Yerdiano; Tasya Wulandari; Othniel Jevon Wibowo; Lilik Ariyanti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Hypertension, or high blood pressure, is a chronic condition characterized by persistently elevated pressure within the arterial walls. The prevalence of hypertension among older adults continues to increase as life expectancy rises, highlighting the need for sustained preventive and health promotion efforts. This community service program aimed to improve the knowledge and awareness of elderly residents at Widhi Asih Nursing Home, Surakarta, regarding hypertension prevention and management. The intervention included baseline blood pressure screening, elderly exercise sessions, interactive health education based on the